Post‐Synthetic Anisotropic Wet‐Chemical Etching of Colloidal Sodalite ZIF Crystals. Issue 48 (12th October 2015) - Avci, Civan; Ariñez‐Soriano, Javier; Carné‐Sánchez, Arnau; Guillerm, Vincent; Carbonell, Carlos; Imaz, Inhar; Maspoch, Daniel
Abstract: Controlling the shape of metal–organic framework (MOF) crystals is important for understanding their crystallization and useful for myriad applications. However, despite the many advances in shaping of inorganic nanoparticles, post‐synthetic shape control of MOFs and, in general, molecular crystals remains embryonic. Herein, we report using a simple wet‐chemistry process at room temperature to control the anisotropic etching of colloidal ZIF‐8 and ZIF‐67 crystals. Our work enables uniform reshaping of these porous materials into unprecedented morphologies, including cubic and tetrahedral crystals, and even hollow boxes, by an acid–base reaction and subsequent sequestration of leached metal ions. Etching tests on these ZIFs reveal that etching occurs preferentially in the crystallographic directions richer in metal–ligand bonds; that, along these directions, the etching rate tends to be faster on the crystal surfaces of higher dimensionality; and that the etching can be modulated by adjusting the pH of the etchant solution. Abstract : Post‐synthetic wet‐chemical anisotropic etching of colloidal ZIF‐8 and ZIF‐67 crystals enables uniform reshaping of them into unprecedented shapes, including cubic and tetrahedral crystals, and even hollow boxes, by an acid–base reaction and subsequent sequestration of leached metal ions.